2015
DOI: 10.1007/s12011-015-0478-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of PTEN-Akt-CREB Signaling Pathway in Nervous System impairment of Rats with Chronic Arsenite Exposure

Abstract: The nervous system is a target of arsenic toxicity. Phosphatase and tensin homologue deleted on chromosome 10/protein kinase B/cAMP-response element binding protein (PTEN/Akt/CREB) signaling pathway has been reported to be involved in maintaining normal function of the nervous system, modulating growth and proliferation of neurocyte, regulating neuron synaptic plasticity, and long-term memory. And many studies have demonstrated that expressions of PTEN, Akt, and CREB protein were influenced by arsenic, but it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The gene for phosphatase and tensin homolog (PETN), which is located on human chromosome 19, encodes a dual phosphatase enzyme that dephosphorylates both protein and lipid substrates [16]. Also, PTEN is a negative regulator of the phosphatidylinositol 3-kinase/protein kinase B (PI3K/ Akt) signaling pathway [17], which is implicated in hypoxicischemic injury [18]. However, it has been unclear whether bone marrow mesenchymal stem cells (BMSCs)-derived exosomes and miR-29b-3p moderate the severity of ischemic brain injury and whether their regulation is dependent on PTEN or the Akt signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The gene for phosphatase and tensin homolog (PETN), which is located on human chromosome 19, encodes a dual phosphatase enzyme that dephosphorylates both protein and lipid substrates [16]. Also, PTEN is a negative regulator of the phosphatidylinositol 3-kinase/protein kinase B (PI3K/ Akt) signaling pathway [17], which is implicated in hypoxicischemic injury [18]. However, it has been unclear whether bone marrow mesenchymal stem cells (BMSCs)-derived exosomes and miR-29b-3p moderate the severity of ischemic brain injury and whether their regulation is dependent on PTEN or the Akt signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that toxins, such as propofol and arsenic, could impair basal synaptic transmission, hippocampal LTP, and memory, along with decreased p-Akt levels. 32,33 Our results showed that p-Akt was significantly downregulated in 3.5 nm MPA-modified CdTe QD exposure, which indicated that dysfunction of the PI3K-Akt signaling pathway might be one of the mechanisms of CNS impairment induced by MPA-modified CdTe QD exposure. However, the effects of 3.5 nm MPA-modified CdTe QDs on the phosphorylation of Akt are complicated in view of the findings that the mRNA level of the gene PIK3R5 (encoding PI3K) was significantly upregulated in high-dose 3.5 nm MPA-modified CdTe QD exposure, and decreased p-Akt levels were not dose-dependent.…”
mentioning
confidence: 69%
“…Three groups received 5, 10, 50 mg/L sodium arsenite for six consecutive months, and the other three groups received 5, 10, 50 mg/L sodium arsenite for 3 months and then received distilled water for another 3 months (Figure 1 ). Our pilot study provided an appropriate drug for this study (Zhang et al, 2013 ; Qu et al, 2016 ). All rat experiments were in strict accordance with the Chinese legislation on the use and care of laboratory animals and were approved by the University committees for animal experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the membranes were incubated for 1 h with Goat anti rabbit IgG antibody conjugated to alkaline phosphatase (1:1000 dilution; Zhongshan Golden Bridge Biotechnology, China) as the second antibody. The band was visualized after reacting with Western Blue Stabilized Substrate for Alkaline Phosphatase (Promega, Madison, WI, USA) for a moment and was photographed by Tanon GIS-2020 gel image processing system (Shanghai Tanon Technology, China; Qu et al, 2016 ). The results were expressed as a relative optical density and analyzed using ImageJ software.…”
Section: Methodsmentioning
confidence: 99%